SERIAL CASES INTRAVITREAL TENECTEPLASE AND PNEUMATIC DISPLACEMENT OF SUBMACULAR HEMORRHAGE: Poster Presentation - Case Series - Ophthalmologist - Dewi, Upik Mahna (Majalah Oftalmologi Indonesia, 2023)
Introduction : OBJECTIVE Submacular hemorrhage SMH is uncommon complication of choroidal or retinal vascular abnormalities, including choroidal neovascularization CNV, polypoidal choroidal vasculopathy PCV and retinal macroaneurysm of these, PCV is condition most frequency associated with large SMH {reported in 20%-63% of eyes with PCV} PURPOSE To presence successful management of submacular hemorrhage with combination injection intravitreal IVT Tenecteplase and gas C3F8 100% Case Illustration : METHODES All patient with SMH already take foto fundus and OCT pre and post IVT methalyse and gas C3F8 100%. All patients undergone IVT gas C3F8 100% 0.2 cc and take a rest for 20 second after that IVT methalyse 0.1 cc was injected. Positioning 1st 24 hours: Free Positioning, 2nd 24 hour: Positioned face down, 3rd days: Follow up. Discussion : RESULT The submacular hemorrhage move out from macular for all of cases. Vision improvement occourred in all cases. Conclusion : CONCLUTION Intravitreal Tenecteplase in conjunction with pneumatic displacement appears effective in displacing submacular blood.